Characterisation of the soundscape of parks and green areas through the triangulation of methodologies proposed by ISO/TS 12913-2 - Engel, Margret Sibylle; Szeremeta , Bani; Maciel, Karoline Farias Koloszuki; Zannin, Paulo Henrique Trombetta (Revista Nacional de Gerenciamento de Cidades, 2021)
The management of urban spaces and environmental health has been growing in recent years, and the sound aspects were highlighted during the Coronavirus pandemic (COVID-19). Locations that generally showed noises from vehicle traffic presented a diversity of sounds, generally not perceived in everyday situations before the pandemic. Awareness of the sound impacts generated before the pandemic has provided a broad discussion between the scientific community and managers regarding developing tools to improve urban planning and environmental health in cities. This study aims to characterise the soundscape of two parks in Curitiba by triangulating evaluation methodologies proposed in the ISO/TS 12913-2 (2018). Such triangulation included the descriptive analysis of objective and subjective sound data, analysis and elaboration of sound and perception maps, providing a systemic overview of the sonic environment of the investigated parks.